2017
DOI: 10.1080/02670844.2016.1248119
|View full text |Cite
|
Sign up to set email alerts
|

Modification of ZTA particles with Ni coating by electroless deposition

Abstract: The modification of ZTA particles with Ni coating as reinforcement is systematically clarified to enhance the wearability of Ni-encapsulated ZTA (ZTA@Ni)-reinforced high-chromium cast iron (HCCI) matrix composites. Continuous and uniform metallic Ni coatings are formed on ZTA surface by electroless deposition with ChCl-EG ionic liquid as additive. The coating thickness can be controlled by regulating deposition times and the ZTA@Ni particles with 24.35 μm are chosen as reinforced phase in HCCI matrix composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…The specific surface area of the ZTA particles was determined to be approximately 0.99 m 2 g −1 by Brunauer‐Emmett‐Teller (BET) analysis (Micromeritics ASAP 2060 model). The matrix material is HCCI, and its components have been reported in our previous work …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific surface area of the ZTA particles was determined to be approximately 0.99 m 2 g −1 by Brunauer‐Emmett‐Teller (BET) analysis (Micromeritics ASAP 2060 model). The matrix material is HCCI, and its components have been reported in our previous work …”
Section: Methodsmentioning
confidence: 99%
“…Fabrication of the Ni‐Encapsulated ZTA Particles : First, the ZTA particles were pretreated as reported in our previous work . Then, the electroless deposition of Ni on the ZTA particles was performed in a nickel electroless bath.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have found that the contact angles of Fe/Al 2 O 3 and Fe/ZrO 2 reach 140°and 116°, respectively [11,12].This shows that the interface bonding ability between Fe and the two ceramic materials is very poor. Therefore, it is necessary to modify ZTA particles by metal coating [13].…”
Section: Introductionmentioning
confidence: 99%
“…Electroless plating is widely used as a surface metal coating treatment method in the manufacture of cermets [13][14][15][16].The metal coating on the ceramic surface is mutually soluble or reacted with the matrix metal to obtain a mechanical bonding interface or a reaction bonding interface to achieve a wetting effect. Ru et al [16] found electroless plated Ni and Cr on the surface of ZTA, and Ni and Cr diffused into the iron matrix under high temperature conditions, forming a diffusion interface layer, which improved the wettability of ZTA and matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Du J. studied the ZTA ceramic particle reinforced high chromium cast iron composites (HCCI) with a honeycomb structure obtained by infiltration casting and acquired the best casting process parameters by a finite element calculation [19]. The wear resistance results of the composites with honeycomb structure are better than that of the metal matrix [20,21].…”
Section: Introductionmentioning
confidence: 99%